Jarak Penempatan Lightning Arrester sebagai Pelindung Transformator terhadap Tegangan Lebih pada Gardu Induk 150 Kv Harapan Baru - Toyib; M. Zainuddin; Rusdiansyah; Bustani; La Bima (PT. PENERBIT TIGA MUTIARA, 2023)
The substation is part of the electrical energy distribution system, therefore depending on its function it must be protected from disturbances that cause disruption to the distribution of electrical energy. One of the important equipment in a substation is a transformer, and the protection device used is a lightning rod. With its good characteristics, the arrester plays a role in bypassing lightning currents so that the equipment does not produce high overvoltages. The analysis results show that the maximum distance between the arrester and the transformer is 10.96 meters, while the installation distance in the field is 3.2 meters, so the arrester can still protect the transformer because it is still lower than the maximum distance. Allowed. After the arrester turns on for 9.54 μs, the voltage on the transformer will drop. And because the BIL of the transformer is 650 KV and the peak voltage reaches 751.3 kV at 300 μs, the arrester can still protect the transformer.